Forging Ideal Muslim Subjects: Discursive Practices, Subject Formation, & Muslim Ethics (by Faraz Masood Sheikh) (American Journal of Islam and Society, 2022)
In the fields of Muslim ethics and comparative religious ethics over the past two decades, embodiment and embodied practices have reigned as rich methodological loci yielding numerous illuminating studies on the nature and process of ethical formation, in large part because of the pioneering work of anthropologist of Islam, Talal Asad. But as is often the case with scholarly methodologies, the pendulum has begun to swing back, in this case towards an interest in theological and philosophical reasoning as crucial to understanding how religious and moral selves are formed—for example, in Thomas A. Lewis’s 2016 Why Philosophy Matters for the Study of Religion & Vice Versa. Presenting himself as standing firmly in the camp of this nascent trend, Faraz Masood Sheikh offers his Forging Ideal Muslim Subjects: Discursive Practices, Subject Formation, and Muslim Ethics as a study of both Muslim and comparative religious ethics that takes the power of ideas and reasoned reflection seriously in ethical formation. Sheikh seeks to demonstrate this primarily through an analysis of the thought of two important and understudied Muslim thinkers, the ninth-century moral pedagogue, al-Ḥārith ibn Asad al-Muḥāsibī (d. 243/857) and the twentieth-century Kurdish Qur’an scholar, Bediüzzaman Said Nursi (d. 1960).